Hadoop the definitive guide - White, Tom (O'Reilly, 2012)
Annotation
Includes bibliographical references and index. - Print version record
Keywords: Apache Hadoop; File organization (Computer science); Apache Hadoop (Computer file); Fichiers (Informatique); Organisation